The role of T regulatory cells in the immunopathogenesis of HIV: Clinical implications - Giti Esmail Nia; Marzieh Mohammadi; Maedeh Sharifizadeh; Ghasem Ghalamfarsa; Azam Bolhassani (Brazilian Journal of Infectious Diseases, 2024)
Human Immunodeficiency Virus (HIV) infection is among the most challenging issues in the healthcare system, presenting significant financial and hygiene problems with a wide range of clinical manifestations. Despite the hopeful outcomes of Antiretroviral Therapies (ARTs), the current strategies for the treatment of patients with HIV infection have not shown clinical significance for all subjects, which is mainly due to the complexity of the disease. Therefore, the need for collaborative and interdisciplinary research focused on deciphering the multifaceted cellular, and molecular immunopathogenesis of HIV remains essential in the development of innovative and more efficacious therapeutic approaches. T-regulatory (Treg) cells function as suppressors of effector T-cell responses contributing to the inhibition of autoimmune disorders and the limitation of chronic inflammatory diseases. Notably, these cells can play substantial roles in regulating immune responses, immunopathogenesis, viral persistence and disease progression, and affect therapeutic responses in HIV patients. In this review, we aim elucidating the role of T-regulatory cells (Tregs) in the immunopathogenesis of HIV, including immunological fatigue and seroconversion. In particular, the focus of the current study is exploration of novel immunotherapeutic approaches to target HIV or related co-infections.